पोखराको बिस्केट जात्राः विगत र वर्तमान {Bisket Jatra of Pokhara: Past and Present} - Shrestha, Laxman (Nepalese Culture, 2023)
The present article is based on the title "Biscuit Jatra of Pokhara: Past and Present". The Newar community, established in Kathmandu Valley as the original settlement, has been making its Karmabhoomi (land of action) in various places outside Kathmandu. Some Newar communities have come and settled in Pokhara Valley. During this migration, the Newar community brought various cultural fairs and festivals with them. The Bisket Jatra (festival) at Pokhara is one of them. What are the changes that have occurred in the past and present of Bisket Jatra in Pokhara? How do you celebrate Biscuit Jatra in Pokhara? The major focus of this research rests on these two questions.in this article. The main purpose of this article is to investigate these two main questions. To fulfill the objective, the researcher has used qualitative research method. The analysis of this research has shown that while celebrating Bisket Jatran here at Pokhara, people stay at home to celebrate the Bhoj associated with the festival, but, besides that, there is no significant participation in the Jatra in comparison to the past.